An Efficient Protocol for Successful in Vitro Propagation of Cardiospermum halicacabum: An Ornamental Plant with Medicinal Powers Growing in the Jordanian Environment - Al-Shayeb, Dalal; Tahtamouni, Reham; Shatnawi , Mohamad; Abu Saim, Asma’a Ayob (Jordan Journal of Agricultural Sciences, 2025)
Cardiospermum halicacabum is an ornamental plant known for its significant medicinal benefits. It is utilized in the treatment of various ailments, including rheumatism, neurological disorders, and snakebites. However, overgrazing and poor seed germination are the main constraints for C. halicacabum propagation and sustainability. Tissue culture can be applied as an efficient technique for increasing and conserving this plant. In this research, the effect of several growth regulators and pH levels on C. halicacabum micropropagation was investigated. For shoot proliferation growth regulators (Benzyl Amino Purine (BAP), zeatin, and kinetin) at different levels (0.0, 0.4, 0.8, 1.2, 1.6, and 2.0 mg/L) were tested to enhance shoot development in C. halicacabum. Benzyl Amino Purine (BAP) was found to be the most effective hormone for shoot multiplication at (0.8 mg/L) BAP, which produced 3.89 shoots. Meanwhile, pH ranging from 4.0 to 6.0 did not show any significant difference related to in vitro propagation. For rooting, indole acetic acid (IAA), naphthalene acetic acid (NAA), and indole-3-butyric acid (IBA) at (0.0, 0.4, 0.8, 1.2, 1.6, and 2.0 mg/L) were tested. IAA was the best growth regulator used for rooting of C. halicacabum. Most plantlets (90%) were acclimatized under greenhouse conditions. Our data demonstrate a successful in vitro propagation method of C. halicacabum. This would encourage further research work on C. halicacabum, such as investigating its active ingredients and antimicrobial powers.